Органи місцевого самоврядування як суб’єкт запобігання злочинам : автореф. дис. - Шеремет, О. С.; Sheremet, O. S. (Харків, 2018)
Дисертація є першим в Україні комплексним науковим дослідженням, в якому з урахуванням законодавства, досягнень теорії і практики, висунуто низку концептуальних у теоретичному та прикладному аспектах положень і висновків, які визначають поняття органів місцевого самоврядування як суб’єкту запобігання злочинам, розкривають їх місце, роль та функції. Показано причинно-наслідковий зв’язок між показниками злочинності та участю органів місцевого самоврядування у запобіганні злочинам. Констатовано, що охорона громадського порядку та профілактика правопорушень на регіональному рівні повинні бути віднесені до числа питань місцевого значення, що відповідало б положенням Конституції України. На цій основі запропоновано доцільність наділення органів місцевого самоврядування організаційною та координуючою функціями, щодо діяльності правоохоронних органів, що зможе обмежити пріоритет відомчих інтересів, усунути виникаючі протиріччя та неузгодженості в роботі. Доводиться доцільність використання муніципальної поліції при запобіганні окремих видів злочинів. Обґрунтовано необхідність взаємодії органів місцевого самоврядування, державної кримінально-виконавчої служби та органів пробації.

The thesis is the first complex scientific research in Ukraine in which, taking into account legislation, theoretical and practical achievements, a number of conceptual positions and conclusions in theoretical and applied aspects are put forward, in which the current state of development of the local governments bodies, their place, role and functions in the general structure of subjects of crime prevention, in the prevention of certain types of crimes, are revealed. A cause-and-effect relationship between crime rates and the participation of the local government bodies in crime prevention is shown. Based on the analysis of crime in Ukraine, the thesis was formulated that the state policy of promoting the development of civil society in Ukraine should be aimed at using the capacity of the local government bodies to ensure non-conflict relations in ethno-national, cultural and religious spheres, expanding of social intersectional partnership between the government, business and civil society institutions. It is the local government that can create the conditions for direct involvement in the preparation of management decisions of interested public groups, which will contribute to ensuring public consent, social peace, sustainable development and stability in the state. In the course of the study, on the basis of the developed methodology of identification and evaluation of communication between the local government bodies and law enforcement agencies, the public, the theoretical and practical importance of the participation of the local government bodies, as an independent subject, in crime prevention by power balancing between the authorities and executive bodies, was proved. The analysis of current legal framework for regulation of powers of the local government bodies to ensure the prevention of crime is presented and the ways and methods for its improvement are clarified. It was stated that the maintenance of public order and the prevention of offenses at the regional level should be attributed to the issues of local importance, which would comply with the provisions of the Constitution of Ukraine. Pursuant thereto, the content of powers of the local government bodies and the territorial community for the prevention of crimes was differentiated. These powers are reflected in the separation of powers functioning on the principles of democracy in the system of supreme legislative and executive bodies. Since the local government bodies are a concentrated expression of the power of local communities, they are independent in resolving issues within their competence. At the same time, the local government bodies are responsible to the voters, including for organization of safety of the citizens and prevention of crimes at the regional level. The expediency of empowering the local government bodies with organizational and coordinating functions in relation to the activities of the law enforcement agencies has been proved. It is indicated that since most of the crime-preventive-actions of the law enforcement agencies coincide, and their functions overlap, in the context of decentralization, there is a need for a single coordinating body that can limit the priority of departmental interests and eliminate the contradictions and inconsistencies in work. Therefore, among the most important issues that should be resolved by the local government bodies, should be the issues of law enforcement. On this basis, it was proposed to use the municipal police in the prevention of crime in general, and certain types of crimes. A holistic view of an extensive system of measures to improve the prevention of crimes at the regional level in its individual areas, notably, regulatory, organizational, informational, was formed. The theoretical position was substantiated, which determines that the construction of an effective crime prevention system is possible under conditions of partial restriction of human rights and the priority of the interests of collective security in comparison with individual rights. At the same time, it was stated that modern crime prevention measures should not limit the right to life, freedom of speech, protection from torture and illtreatment, from discrimination on all grounds, as well as the right to use legal protection, including judicially. The necessity of interaction between the local government bodies, the state penitentiary service and probation bodies, their mutual assistance in the safe functioning of the penitentiary institutions located in each region is substantiated. It is indicated that since the society is responsible for its citizens, who are held in penitentiary institutions, the functions of control and supervision of the rights and freedoms of both convicts and the staff should be assigned to the local government bodies. The directions for assistance and interaction with the probation bodies and penal institutions have been identified. In the XXI century, the creation of a reliable crime prevention system should be one of the priorities of the state policy to ensure the safety of society. Despite the seeming invincibility of crime, especially fixed in the public consciousness, the local government bodies need to revive morality, restore legal ideology and form respect for criminal law.

Диссертация является первым в Украине комплексным научным исследованием, в котором с учетом законодательства, достижений теории и практики, выдвинут ряд концептуальных в теоретическом и прикладном аспектах положений и выводов, которые определяют понятие органов местного самоуправления как субъекта предупреждения преступлений, раскрывают их место, роль и функции. Виявлена и представлена причинно-следственная связь между показателями преступности и участием органов местного самоуправления в предупреждении преступлений. Констатировано, что охрана общественного порядка и профилактика правонарушений на региональном уровне должны быть отнесены к числу вопросов местного значения, что соответствовало бы положениям Конституции Украины. На этой основе предложено наделить органы местного самоуправления организационной и координирующей функциями по отношению к деятельности правоохранительных органов, что сможет ограничить приоритет ведомственных интересов, устранить возникающие противоречия и несогласованности в работе. Указывается на целесообразность использования муниципальной полиции при предотвращении отдельных видов преступлений. Обоснована необходимость взаимодействия органов местного самоуправления с государственной уголовно- исполнительной службой и органами пробации.
Local government bodies as a subject of crime prevention
Органы местного самоуправления как субъект предупреждения преступлений
Шеремет, О. С. Органи місцевого самоврядування як суб’єкт запобігання злочинам : автореф. дис. ... д-ра. юрид. наук (докт. наук) : 12.00.08 / О. С. Шеремет ; МВС України, Харк. нац. ун-т внутр. справ. - Харків, 2018. - 35 с.
Keywords: Кримінологія. Criminology. Криминология; Автореферати дисертацій. Abstracts of Theses. Авторефераты диссертаций; 12.00.08; органи місцевого самоврядування; органы местного самоуправления; local government bodies; запобігання злочинам; правоохоронні органи; предотвращение преступлений; правоохранительные органы; crime prevention; Україна. Ukraine. Украина; муніціпальна поліція; правоохранительные органы; law enforcement agencies; территориальная община; взаимодействие; взаємодія; interaction; territorial community; територіальна громада